ANALISIS KOINTEGRASI PASAR MODAL IN- DONESIA DENGAN PASAR MODAL AMERIKA SERIKAT DAN PASAR MODAL EROPA MENGGUNAKAN PENDEKATAN JOHANSEN COINTEGRATION TEST (Studi Kasus pada saat terjadi Krisis Ekonomi di Amerika Serikat dan Eropa tahun 2008 - 2012) - Wibowo, Hardianto (Magister Manajemen, Fakultas Ekonomika dan Bisnis Undip, 2012)
By understanding the cointegration between one capital market with other capital markets, it can assist investors in determining which of the capital market will be used to form the International diversification in order to provide a potential advantage. In research on the cointegration of capital markets has been done by Fratzscher (2002), Murtini and Ekawati (2003), Karim, Kassim, dan Arip (2010), Srikanth and Aparna (2012), by taking a few sample of some of the capital market in the world revealeddifferent results, instead of giving rise to a research gap. Therefore, it is necessary to do a deeper study because a different result occured after the economic crisis of United States and Europe in 2008. Research problem to be studied is to analyze the cointegration between the Indonesian capital market with the U.S. capital markets (DJIA) and the European capital markets (FTSE 100, IBEX 35 and ATHEX).This reseach method uses quantitative research. The sample of research is the data from IHSG, DJIA index, FTSE 100 index, IBEX 35 index, and ATHEX index that limited in weekend closing data during the observation period between 2008-2012. Data analysis techniques using Johansen Cointegration Test, Augmented Dickey-Fuller (ADF) Test and Granger Causality Test within 5% significance.The results of this study would be indicate that the Indonesian capital market has been cointegrated with U.S. stock market (DJIA), UK stock market (FTSE 100), Spain stock market (IBEX 35) and Greek capital market (ATHEX). Indeed, the Indonesian Capital Market connected to U.S. and Europe Capital Markets have a causal relationship.